UNRELIABLE M/M/1/2 QUEUEING SYSTEM WITH MASS CUSTOMERS DEPARTURE AND ITS SOLVING - Dorda, Michal (Doprava a spoje, 2009)
The queueing theory is widely used in many branches, for example in informatics, economics and of course in transport. Common models of queueing systems usually assume that a server breakdown can not occur. In this paper the model of the unreliable M/M/1/2 queueing system with mass customer departure after server breakdown occurrence is presented. This paper shows solving of studied model by two different approaches - method according to A. Chincin and by graph method.